(untitled) (Economic studies journal, 2023)
This study investigates the relationships between board size and firm performance. An OLS regression model was used to analyses 225 non-financial UK companies listed in FTSE 350. The time period considered was seven years (2015 to 2021). Return on Assets and Return on Equity were used as proxy of firm performance. The research finds that there exists a positive association between board size and firm performance, implying that in UK allowing board size to be dependent of firm size tends to improve firm performance. Regarding Covid 19 pandemic the investigation depicted that Covid 19 exerts a significant negative impact on firm performance. However, the investigation revealed that the board size had significant and positive impact on firm performance during Covid 19. This result indicate that the board size should be consider to recover the corporate sector in any crisis. This study provides a unique contribution to the literature of board size and firm performance and the role of Covid 19 pandemic.